25-GAUGE TROCAR CANNULA FOR ACUTE ENDOPHTHALMITIS-RELATED IN-OFFICE VITREOUS TAP AND INJECTION: Patient Comfort and Physician Ease of Use. Issue 4 (April 2017) - Vahedi, Sina; Adam, Murtaza K.; Dollin, Michael; Maguire, Joseph I.
Abstract : Purpose: To assess comfort and procedural facility using a 25-gauge trocar cannula as a port to diagnose and treat acute endophthalmitis compared with a standard vitreous tap and injection technique. Methods: Eighteen consecutive patients with acute endophthalmitis were randomized into two treatment arms: 1) Standard vitreous tap and injection technique, and 2) A technique where a valved 25-gauge trocar cannula is inserted through the pars plana as done in sutureless vitrectomy surgery and subsequent vitreous sampling and injections are performed through the port. A standardized anesthetic protocol was used and subjects were masked to the technique performed. Primary outcomes measured were patient comfort using a Wong–Baker pain scale and standardized physician ease-of-use scoring scale. Secondary outcomes included vitreous sampling success rate and volume of vitreous sample. Results: No significant differences were found when comparing patient comfort ( P = 0.340), physician ease-of-use scores ( P = 0.796), vitreous sample volume ( P = 0.149), successful vitreous taps ( P = 0.620), and microbiologic yield ( P = 1.000) between treatment arms. There were no adverse events. Conclusion: The 25-gauge trocar technique provides a safe, well-tolerated, and equally effective alternative to the standard vitreous tap and injection technique for delivery of intravitreal antibiotics, and procuring of vitreous sample, requiring a single sharp penetration. Abstract : The authors report the results of a prospective study showing that using a 25-gague trocar cannula as a port for vitreous tap and injections is equivalent concerning patient discomfort and procedural ease compared with the standard vitreous tap and injection technique.